Quand la distance reconfigure la pratique clinique. Une analyse multimodale des interactions en télémédecine - Sylvie Grosjean; Maria Cherba; Isaac Nahón-Serfaty; Luc Bonneville; Richard Waldolf (Communiquer)
The purpose of this article is to understand the configuration of communication and sensory activity during clinical teleconsultations. To do this, we present a research conducted in collaboration with a simulation laboratory to study the interactions that occur during teleconsultations. By conducting a multimodal analysis of video recordings of orthopaedic teleconsultations, we describe how physicians reorganize their communicative and sensory activity by organizing the teleconsultation space to create a “shared place”. Doing so, they allow the practical accomplishment of “sensing-at-distance”.